Hands-On Application Penetration Testing with Burp Suite : Use Burp Suite and its features to inspect, detect, and exploit security vulnerabilities in your web applications /: Use Burp Suite and its features to inspect, detect, and exploit security vulnerabilities in your web applications. (2019) - Lozano, Carlos A; Shah, Dhruv; Ahemed Walikar, Riyaz
No abstract available